Sasa guangdongensis, a new synonym of Acidosasa carinata (Poaceae: Bambusoideae) - Li, Xing; Tong, Yi-Hua; Xia, Nian-He (Phytotaxa, 2022)
Sasa guangdongensis is a little-known species, which was not treated in Flora Reipublicae Popularis Sinicae or Flora of China. Based on examination of herbarium specimens and fresh material, it is confirmed that Sasa guangdongensis is conspecific with Acidosasa carinata. Thus, the former is treated as a synonym of the latter. The lectotypes for S. guangdongensis and A. carinata are designated. Taxonomic notes on this species are also provided.